Analysis of the strategies for the commercialization of electric energy of generating agents in the short term environment - Mendonça, Anny Key de Souza; Silva, Silvio Aparecido da; Pereira, Luísa Zeredo; Bornia, Antonio Cezar; Andrade, Dalton Francisco de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The development of the electric energy market has gained visibility due to the recent transformations in energy policies in Brazil and worldwide. For many years, investments were not made in the Brazilian electricity sector, causing a delay in the energy matrix. With this, the government implemented measures for structural and institutional reforms in the electricity sector with the objective of guaranteeing the expansion of the generating park, attracting private investment, and promoting market competition. The restructuring of the electricity sector led to the emergence of new ways to negotiate energy, new structures and entities, with the objective of increasing transparency, competitiveness and efficiency among market agents. In the new model of the Brazilian Electricity Sector (SEB), energy trading is carried out through two contracting environments, the Regulated Contracting Environment (ACR) and the Free Contracting Environment (ACL). This research analyzes the electric energy commercialization strategies through generation agents acting and competing in the short-term energy market, through the use of competitiveness graphs.